“THE ANALYSIS AND MEASURING THE NOISE ON THE A2 MOTORWAY (E-65) MOTHER THERESA, SECTION: SKOPJE – TETOVO” - Mijoski, G., Moslavac D., Krakutovski Z., Samardzioska T. (Journal of Croatian Association of Civil Engineers “GRAĐEVINAR” ISSN (printed version): 0350-2465 ISSN (electronic version): 1333-9095 DOI: https://doi.org/10.14256/JCE.1680.2016 Vol. 72, year 2020, Issue 3, pp. 253 – 262 Impact factor (2019) IF=0,599 / 5 year IF=0,689, 2020)
This paper presents measuring the impact of traffic noise on the environment on A2 motorway (E-65) "Mother Teresa" section: "Skopje - Tetovo" in the Republic of Macedonia. Presented measurements were conducted in 2003 when the road was put into exploitation, and then measurements were conducted again in 2014. The noise was estimated according to 2 standards. After establishing the exceeding of the current noise in terms of legislation, solutions and conclusions were proposed in order to overcome the situation.
Keywords: road traffic noise, legislation, methods of calculation, sound map, protective sound barriers, galleries